Identification of low-molecular-weight color contributors of black tea infusion by metabolomics analysis based on UV–visible spectroscopy and mass spectrometry. (30th August 2022) - Cui, Yuqing; Lai, Guoping; Wen, Mingchun; Han, Zisheng; Zhang, Liang
Highlights: Multi-omics analysis was applied in study of black tea color. 425–475 nm was critical absorbance band for black tea color quality. Flavonol glycosides and hydroxycinnamoyl acids contributed to color. Abstract: Nine black tea samples with different color intensity were firstly determined by chromatic difference analyzer. The color characteristics were secondly quantitatively described by UV–visible spectroscopy. Thirdly, liquid chromatography tandem mass spectrometry (LC-MS) based metabolomics analysis was applied in low-molecular-weight compounds. Finally, the color contributors were identified by the correlation analysis of color, spectrometry and mass data. UV–visible based metabolomics analysis revealed that the wavelength at 380–520 nm (VIP > 1.50) was the critical absorbance band for distinguishing different color of BT infusions, while LC-MS based metabolomics analysis indicated that there were 48 main marker compounds responsible for the classification of different BT infusions. Correlation analysis results showed that the coefficients of theaflavins, thearubigins, theabrownins, flavonoid glycosides, and some hydroxycinnamoyl acids were > 0.7, which suggested they were main color contributors of BT infusion. The present study expanded a new vision on the color analysis of BT infusion.